PENINGKATAN HASIL BELAJAR PJOK MATERI PERGAULAN SEHAT MENGGUNAKAN METODE PEMBELAJARAN PENDEKATAN SAINTIFIK - Meri Haryani; Nurkhoiroh Nurkhoiroh; I Kadek Suardika; Arief Ibnu Haryanto; Khoirul Anwar Pulungan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Based on the problems presented by the researcher, the number of students who have low learning outcomes, only (10 students or 40%) who get grades above KKM (60) of 25 students of class XI IPA 2 SMAN 2 Muaro Jambi, and the rest (15 people or 60 or 60 %) does not reach the value of KKM (60). The purpose of this classroom action research is to improve the learning outcomes of PJOK Healthy social material using the learning method of scientific approaches in class XI IPA 2 SMAN 2 Muaro Jambi Academic Year 2021/2022. This type of research is a classroom action research (CAR) as many as two cycles. Each cycle consists of four stages, namely planning, implementation, observation, reflection. The subjects referred to in this study were students of class XI IPA 2 SMAN 2 Muaro Jambi, totaling 25 students and participants involved in this study were the teacher of colleagues, Kiki Kurniawan, S.Pd. The study time was conducted in the odd semester of the 2021/2022 school year in November 2021. The data collected is quantitative and qualitative data. Observations were made using sheets of paper, questionnaires, and notes, after which the data were analyzed using data reduction and percentages. From the results of the analysis it can be concluded that the application of the scientific learning approach has a positive influence, can improve student learning outcomes shown from the data obtained in the first cycle of student learning outcomes which is complete at 40% increases to 92% in cycle II. The action taken by the teacher is to give re -ords in the form of a kind of food gift and provide a true story that occurs in the home environment about healthy social material.